Preventing White Adipocyte Browning during Differentiation In Vitro: The Effect of Differentiation Protocols on Metabolic and Mitochondrial Phenotypes - Elena Herbers; Mimmi Patrikoski; Anita Wagner; Riikka Jokinen; Antti Hassinen; Sini Heinonen; Susanna Miettinen; Hilkka Peltoniemi; Eija Pirinen; Kirsi H. Pietiläinen (Hindawi Limited, 2022)
Mitochondrial dysfunction in white adipose tissue is strongly associated with obesity and its metabolic complications, which are important health challenges worldwide. Human adipose-derived stromal/stem cells (hASCs) are a promising tool to investigate the underlying mechanisms of such mitochondrial dysfunction and to subsequently provide knowledge for the development of treatments for obesity-related pathologies. A substantial obstacle in using hASCs is that the key compounds for adipogenic differentiation in vitro increase mitochondrial uncoupling, biogenesis, and activity, which are the signature features of brown adipocytes, thus altering the white adipocyte phenotype towards brown-like cells. Additionally, commonly used protocols for hASC adipogenic differentiation exhibit high variation in their composition of media, and a systematic comparison of their effect on mitochondria is missing. Here, we compared the five widely used adipogenic differentiation protocols for their effect on metabolic and mitochondrial phenotypes to identify a protocol that enables in vitro differentiation of white adipocytes and can more faithfully recapitulate the white adipocyte phenotype observed in human adipose tissue. We developed a workflow that included functional assays and morphological analysis of mitochondria and lipid droplets. We observed that triiodothyronine- or indomethacin-containing media and commercially available adipogenic media induced browning during in vitro differentiation of white adipocytes. However, the differentiation protocol containing 1 μM of the peroxisome proliferator-activated receptor gamma (PPARγ) agonist rosiglitazone prevented the browning effect and would be proposed for adipogenic differentiation protocol for hASCs to induce a white adipocyte phenotype. Preserving the white adipocyte phenotype in vitro is a crucial step for the study of obesity and associated metabolic diseases, adipose tissue pathologies, such as lipodystrophies, possible therapeutic compounds, and basic adipose tissue physiology.